COMPOSED APPROACH TO IMAGE OBJECT RECOGNITION - Shkurat, Oksana (Collection of scientific papers «ΛΌГOΣ», 2022)
The reason for the rapid development of pattern recognition information technologies is the need for high-quality automation of the real-time processes in manufacture [1-4], robotics (grasping, manipulation, human-robot interaction etc.) [5], medicine [6-8] etc. Therefore, the development and the implementation of approaches to the transfer of human cognitive functions by computerized systems is the actual task.